2019
DOI: 10.3390/agronomy9090548
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sewage Sludge Amendments on the Growth and Physiology of Sweet Basil

Abstract: Currently, wastewater treatment plants produce large amounts of sewage sludge. Due to the rich content of organic matter and minerals, sewage sludge can be used as soil amendments for eroded soils. The aim of this work was to assess sewage sludge (SS) in combination with an eroded soil (ES) collected from the North Eastern Romania as growth substrate for sweet basil, and their effect on basil growth and physiology. The experiment was conducted in a greenhouse under controlled environment conditions. The tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 48 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…Consistently with our findings, previous authors [55,56] reported that the synthesis of phenolic compounds in plants depends upon environmental conditions, cultivar and farming practices; among the latter, the application of microorganisms [30] and fertilizers [57] play a significant role. However, the antioxidant synthesis can be encouraged by different types of fertilization [16] and, indeed, the increased content of polyphenols, flavonoids and anthocyanins recorded in the present study under the unconventional fertilized treatments (biosolids, organic and microorganisms), was presumably due to their stimulation effect on secondary metabolism [58]. Moreover, previous researchers reported an increased content of phenolic compounds in basil plants grown on a substrate with a low nitrogen content [59], as a consequence of the reallocation of nitrogen resources for the synthesis of secondary metabolites at the expense of protein synthesis, according to the carbon/nitrogen balance hypothesis [60].…”
Section: Discussionmentioning
confidence: 56%
“…Consistently with our findings, previous authors [55,56] reported that the synthesis of phenolic compounds in plants depends upon environmental conditions, cultivar and farming practices; among the latter, the application of microorganisms [30] and fertilizers [57] play a significant role. However, the antioxidant synthesis can be encouraged by different types of fertilization [16] and, indeed, the increased content of polyphenols, flavonoids and anthocyanins recorded in the present study under the unconventional fertilized treatments (biosolids, organic and microorganisms), was presumably due to their stimulation effect on secondary metabolism [58]. Moreover, previous researchers reported an increased content of phenolic compounds in basil plants grown on a substrate with a low nitrogen content [59], as a consequence of the reallocation of nitrogen resources for the synthesis of secondary metabolites at the expense of protein synthesis, according to the carbon/nitrogen balance hypothesis [60].…”
Section: Discussionmentioning
confidence: 56%
“…Sludge containing essential metal ions and high concentrations of plant-available nitrogen and phosphorus increased the content of assimilatory pigments in basil leaves. According to Burducea et al and Pengcheng et al [89,90], these nutrients are essential for chlorophyll synthesis. In the present study, plants grown on the mixture with the highest content of sewage sludge were characterized by the highest assimilatory activity, as demonstrated by high values of the Fv/Fm ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Plants grown on the above mixture were also characterized by the most rapid growth. Burducea et al [89] analyzed basil plants grown on substrates fertilized with sewage sludge. Sludge containing essential metal ions and high concentrations of plant-available nitrogen and phosphorus increased the content of assimilatory pigments in basil leaves.…”
Section: Discussionmentioning
confidence: 99%
“…One of the valid solutions is the use of sludges in agriculture which implies a series of advantages among which natural nutrient intake, soil texture improvement and even water intake, if sludge distribution is performed before its drying. A particularly delicate aspect is that sludges contain, in addition to various beneficial substances, heavy metals, microorganisms, viruses or other pathogens which represent a potential hazard to human and animal health and to the quality of ecosystems, in case they are used as a fertilizer [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%